HUBUNGAN KEMANDIRIAN BELAJAR DENGAN HASIL BELAJAR MATA KULIAH STATIKA MAHASISWA JURUSAN TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - 781-790 , Oka Febri Rahmad (Universitas Negeri Padang, 2015)
Abstract This research is motivated by the low learning outcomes of the course Statics students of 2013.This research aims to determine the relationship between LearningIndependent with learning outcomes subject Statics and how great relationship LearningIndependent with learning outcomes subject Statics students of Department of Civil Engineering FT UNP. This research descriptive correlational research. The student at 2013 which have taken Statics Lecture half July-December 2013 amounted to 63 studen with used, the sampling method, amounting to total sampling 63 students. The variables in this research are Learning Independent as the variable (X) and learning outcomes Statics dependent variable (Y). Based on the results of data analysis can be stated that there a relationship between Independent Learning with Learning Result Statics course students of Department of Civil Engineering, Faculty of Engineering, State University of Padang. Great relationships 23.52% at 95% confidence level. Keywords:Hubungan, Kemandirian Belajar, Hasil Belajar